Patients’ experiences of atrial fibrillation and comorbidity management in clinical practice: a pan-European qualitative descriptive interview study - Stylianos Tzeis; Edward Baker; Bart A Mulder; Hein Heidbüchel; Geraldine Lee; Lien Desteghe; Rana Önder; Rafal Dabrowski; Stavros Karanikas; Miguel Jauregui-Abularach; Daniel Merino (BMJ Open)
Objective The objective is to explore patients’ perceptions on the management of atrial fibrillation (AF) and associated comorbidities.Design A descriptive qualitative study involving in-depth individual interviews, analysed using Braun and Clarke's approach to Reflexive Thematic Analysis.Setting Cardiology departments in teaching hospitals in five geographically diverse European countries—Belgium, Greece, Poland, Spain and the Netherlands.Participants 30 adults aged 65 years or older, diagnosed with AF, with two or more confirmed comorbidities were interviewed.Results The average age was 73 years, 37% were women and the most common comorbidity was hypertension (n=26, 87%), followed by hypercholesterolaemia (n=12, 40%), obesity (n=10, 33%), hypothyroidism (n=9, 30%) and diabetes (n=7, 23%). Three main themes were identified: (1) navigating the diagnosis path and adapting to life with AF, (2) normalising symptoms and treatment burden and (3) striving to build a therapeutic relationship.Respondents had some knowledge about the relationship between comorbidities and AF but lacked understanding of how these comorbidities related to AF. Participants raised concerns regarding their medications, especially anticoagulants, with a desire to be given more information about them. Participants were motivated to make lifestyle adjustments but reported a lack of education and advice on how to implement and maintain these lifestyle changes. Overall, participants were very satisfied with their cardiology/AF teams, and they emphasised the importance of a person-centred approach. There was a perceived disjointedness to healthcare systems, with some reporting multiple appointments at different locations, leading to participants being frustrated and highlighting the lack of integrated care.Conclusions In-depth interviews provided an excellent platform to explore the perceptions and experiences of patients living with AF and associated comorbidities and highlighted the lack of an integrated approach to multimorbid AF management.